Analýza cestovního ruchu města Zlína a jeho blízkého okolí - Šrámková, Dana (Univerzita Pardubice, 2011)
The article deals with analysis of the situation in the fields of tourism in the town Zlin and its vicinity. The description of the situation in the tourism industry is based on the processing of the basic assumptions of tourism, PEST analysis and subsequent processing and evaluation of a SWOT analysis.
Keywords: tourism; Zlin; prerequisites for tourism development; PEST analysis; SWOT analysis